Comparison of various decalcifying agents to evaluate their efficacy - John, Sharon; Devi, Priya; Sharma, Pooja; Gupta, Shalini; Chandra, Shaleen (International Journal of Basic & Clinical Pharmacology, 2023)
Background: Bone is a biological complex structure primarily comprising collagen and minerals. It is important to demineralize these mineralized tissues to remove their calcium apatite crystals for analysing the sub-cellular, cellular, and fibrillar architecture. Six demineralizing agents’ efficacy was examined by assessing their duration, ease of handling tissue, staining, and histological criteria. The present study aimed to evaluate six commonly used demineralizing agents to identify the best decalcifying agent. Methods: Twenty resected hard tissue specimens (1 cm × 1 cm x 1 cm) from the archives were used in the study. These segments were decalcified by solutions namely 10% nitric acid, 10% formic acid, 14% ethylene di amine tetra acetic acid (EDTA), a mixture of formic acid and hydrochloric acid (formic + HCL) 4% each, and a mixture of formic acid and nitric acid 4% each (formic + HNO3), 10% formal nitric acid further subjected to radiographic endpoint test. Results: The present study confirmed the fact that samples treated with EDTA showed the best overall impression in terms of tissue integrity and histology followed by 10% formal nitric acid which gave fairly good cellular details and was also rapid in the action. Conclusions: Based on the present study findings, we suggest that 10% formal nitric acid is the better decalcifying agent available, considering time and tissue integrity as two main factors.